Kualitas udara disektor industri karung plastik - Arum Yuniari; M. Sri Wahyuni; C. Yuwono Sumasto (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1998)
Air pollution is generated by air pollutant in production. Raw materials used in the production of plastic corrugated sack are Polyethylene and Polypropylene. Polyethylene and Polypropylene yars are knitted to be various plastic knits such as plastic corrugated sacks. The result of this study shows that concentration of dust particles in processing area is 30 – 34 ugr/m3, and in finishing area is 38,6- 972 ugr/m3. The other gases such as Ox, SO2, H2S and NH3 are still low. The overage concentration of dust particle in ambient air is about 38,6 – 380 ugr/m3. However for parameter of Ox, SO2, H2S and NH3 seems stile low. INTISARI Karung plastik merupakan salah satu bentuk pengemas yang sangat penting pada sektor industri. Peningkatan jumlah industri karung plastik memberikan dampak terhadap lingkungan sekitar. Terjadinya pencemaran udara dapat diakibatkan oleh gas buang yang dikeluarkan pada proses produksi. Bahan baku yang dipakai dalam pembuatan karung plastic adalah Polietilen dan Polipropilen. Benang-benang plastic ditenun menjadi aneka tenun plastik, misalnya karung plastik. Hasil penelitian terhadap gas buang pada ruang proses produksi dan ruang finishing masih dibawah nilai ambang batas Hygyene Perusahaan dan Kesehatan Kerja. Konsentrasi udara dilingkungan sekitar yang melebihi ambang batas adalah parameter debu 0,344 – 0,380 mgr / m3. Untuk parameter Ox, SO2, H2, dan NH3 sudah memenuhi baku mutu Kep. 02/MENKLH/I/1988.